Docking Molecular dari Kompleks Zn(II)Amina (Prolin)dithiokarbamat terhadap Reseptor Estrogen-α - Irfandi, Rizal; Ruslang, Ruslang; Raya, Indah; Yani, Ahmad; Nasir, Muhammad; Nurcaya, Nurcaya; Jarre, Sulistiani (Al-Kimia, 2021)
Estrogen-α (ER-α) is a major target in cancer therapy. Targeting the ER-α target protein is known to slow the proliferation of breast cancer cells. The purpose of this study was to determine the interaction of the complex compound Zn(II)Prolinedithiocarbamate against the Estrogen-α Receptor. The Zn(II)Prolinedithiocarbamate complex was predicted canonical SMILE by Cheminfo online application (O=C(O)C1CCCN1C2S[Zn]S2) and modeled with online corina to obtain a three-dimensional structure. The structure of the complex compound Zn(II)Prolinedithiocarbamate interacted with Estrogen receptor alpha protein to test its potential anticancer activity. Molecular docking results show the interaction of the Zn(II)Prolinedithiocarbamate complex with the Estrogen- receptor on the amino acid residues ARG394, LEU387, GLU353, LEU346, LEU349, and PHE404. The Zn(II)Prolinedithiocarbamate complex interacts directly with ER-α in the estrogen region which causes the failure of the interaction between estrogen and the estrogen receptor, so it can be predicted that the Zn complex has activity as an ER-α inhibitor and has the potential to be developed in the treatment of breast cancer.